(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The principle of complementarity under the Rome Statute balances state sovereignty with international criminal accountability but can also limit the ICC’s jurisdiction. This article examines its impact through the cases of Saif Al-Islam Gaddafi and Abdullah Al-Senussi, highlighting challenges in assessing state compliance and ensuring justice in politically unstable regions. While complementarity promotes national prosecutions, it can also shield perpetrators when domestic systems are ineffective. The study argues for clearer criteria in evaluating state willingness and ability, ensuring that complementarity does not hinder the ICC’s mandate to prosecute the most serious crimes.